Sosialisasi Pengelolaan Teaching Farm Pembibitan Kakao Unggul pada Kelompok Tani Kakao se-Kota Padang - Obel Obel; Rachmad Hersi Martinsyah; Armansyah Armansyah; Meisilva Erona Sitepu; Munzir Busniah; Yulmira Yanti; Eka Candra Lina; Nugraha Ramadhan (Warta Pengabdian Andalas, 2023)
Cocoa is a plantation commodity that is essential to the Indonesian economy. There are still many problems in cocoa cultivation found in the field, such as using poor-quality seedlings. One of the ways to do this is by taking preventive action by providing immunity induction from the seedling stage. Immunity induction can be done by utilizing Rhizobacteria, arbuscular mycorrhizal fungi, Entomopathogenic fungi, and vegetable pesticides. The Faculty of Agriculture of Universitas Andalas collaborated with the entrepreneurs through a Ministry of Education and Culture program, Matching Fund 2022, to make an innovation, namely the Teaching Farm for superior cocoa nurseries. This activity aims to socialize the cocoa nursery teaching farm in the hope of helping farmers prepare high-quality and sustainable cocoa seeds. This community service activity has been carried out at the Padang City Agriculture Office. The conclusions of this activity include: a) The community service program made by the Teaching Farm Team of Universitas Andalas is by the needs of the farmer group; the farmer group is satisfied and feels this service activity was helpful for the development of the Cocoa farmer group in the future, b) enrichment of understanding of farmer group members regarding biofertilizers and vegetable pesticides.